Modeling the Inception of Supercontinent Breakup: Stress State and the Importance of Orogens - Huang, Chuan; Zhang, Nan; Li, Zheng-Xiang; Ding, M.; Dang, Z.; Pourteau, Amaury; Zhong, S. (AMER GEOPHYSICAL UNION, 2019)
The relative significance of various geodynamic mechanisms that drive supercontinent breakup is unclear. A previous analysis of extensional stress during supercontinent breakup demonstrated the importance of the plume-push force relative to the dragging force of subduction retreat. Here, we extend the analysis to basal traction (shear stress) and cross-lithosphere integrations of both extensional and shear stresses, aiming to understand more clearly the relevant importance of these mechanisms in supercontinent breakup. More importantly, we evaluate the effect of preexisting orogens (mobile belts) in the lithosphere on supercontinent breakup process. Our analysis suggests that a homogeneous supercontinent has extensional stress of 20–50 MPa in its interior (<40° from the central point). When orogens are introduced, the extensional stress in the continents focuses on the top 80-km of the lithosphere with an average magnitude of ~160 MPa, whereas at the margin of the supercontinent the extensional stress is 5–50 MPa. In both homogeneous and orogeny-embedded cases, the subsupercontinent mantle upwellings act as the controlling factor on the normal stress field in the supercontinent interior. Compared with the extensional stress, shear stress at the bottom of the supercontinent is 1–2 order of magnitude smaller (0–5 MPa). In our two end-member models, the breakup of a supercontinent with orogens can be achieved after the first extensional stress surge, whereas for a hypothetical supercontinent without orogens it starts with more diffused local thinning of the continental lithospheric before the breakup, suggesting that weak orogens play a critical role in the dispersal of supercontinents.